Musculoskeletal Pain Experienced on Most Days is a Common Accompaniment of Ageing amongst Community-Dwelling Older Australians: A Questionnaire-Based Study - Gilmartin-Thomas, Julia F-M.; Ernst, Michael E.; Nelson, Mark R.; Lockery, Jessica; Ward, Stephanie A.; Woods, Robyn L.; Britt, Carlene; Murray, Anne; Workman, Barbara; McNeil, John (Journal of aging and health, 2021)
Objective: To describe the prevalence, location and impact of moderate to severe pain experienced on most days in community-dwelling older (≥70 years) adults who were ASPirin in Reducing Events in the Elderly (ASPREE) clinical trial participants. Methods: Cross-sectional ASPREE Longitudinal Study of Older Persons (ALSOP) data were collected from self-reported questionnaires administered to 16,439 ASPREE participants. Results: Of 14,155 respondents, 41% of males (n = 2651/6475) and 50% of females (n = 3803/7680) reported experiencing pain on most days. One quarter of respondents reported experiencing pain on most days that was moderate or severe in intensity (n = 3560/14,155), commonly located in the lower back, knees and upper back. Of those reporting moderate or severe pain, 51% reported taking analgesic medication on most days (n = 1812/3560), almost one-third also reported regular interference with sleep (29%, n = 1024/3560), walking (35%, n = 1239/3560) and daily activities (41%, n = 1467/3560). Discussion: Lower back, knee or upper back pain is a common accompaniment of ageing.